UTILIZING ICT TO DEVELOP STUDENT’S LANGUAGE ETHIC AT ISLAMIC UNIVERSITY - Eka Apriani; Dadan Supardan; Eka Sartika; Suparjo Suparjo; Ihsan Nul Hakim (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
ICT is tools or medias that facilitate teaching and learning process in the classroom. ICT includes software application, computers, radio, television, telephony, CD ROM, audio or video clips, computer, and internet. Utilizing this technology is not improve students’ achievement but also their character, especially language ethic. Students’ language ethic has relationship to linguistics aspects. In semantics, the study tells about how polite language used to communicate with other people in the real context. In pragmatics, the study tells about how polite language used to communicate with older and younger people based on the situation. There were some words and expressions can be used and can be not used to communicate with other people. One way to teach semantics and pragmatics was used ICT in the calssroom. Using ICT that input islamic value can develop the students’ character indirectly. Hopefully, all of the English Lecturer using ICT as English Teaching Media at Islamic University.